Lived Experiences: Hemodialysis and Adherence - Ford-Anderson, PhD, Carla A. (The Journal of Nephrology Social Work, 2012)
This qualitative study, entailing face-to-face, individual, tape-recorded interviews with a convenience sample of 22 hemodialysis patients, examines their lived experiences regarding adherence to the hemodialysis treatment regimen. The 7 openended questions capture patients’ experiences with coming to treatment, taking medications, and restricting fluids. Content analysis identifies the primary patterns in the data—the themes, words, concepts, and terms that prevail in the responses (Patton, 1990). The findings point out the multidimensional aspects of adherence and patient struggles and challenges, and they may open doors for further research that can identify effective interventions.